KESWACARRI AS AN EFFORT TO INCREASE CADRE CAPABILITY FOR TREATING MENTAL DISORDERS PATIENTS IN THE MODERN INDUSTRIAL COMMUNITY 4.0 - Rizki Fitryasari; RR Dian Tristiana; Ariska Windy; Erlina Dwi Kurniasari (Universitas Airlangga, 2022)
Introduction: The low role of mental health cadres is influenced by internal factors such as commitment, motivation and enthusiasm of cadres in helping to overcome mental disorders in the community. Commitment is the most important thing in carrying out the task. Increasing the commitment of the cadres can be done with KESWACARRI (caring mental health and spirituality) with the aim of building self-commitment using a caring and spirituality approach. Methods: This study used pre-experimental design. The sample of was 30 cadres and caregivers who responsible for mental health patients in Ketidur Village, Mojokerto. The variable measured included commitment, caring and spirituality. The data was collected using questionnaire and the analyzed using SPSS to see the frequency distribution. Keswaccari was given to the cadres by providing material about develop caring behavior with spirituality. Results: The results showed, the level of commitment, caring and spirituality of mental health cadres in 30 respondent’s majority was increasing. These results indicate that there is an influence of Keswaccari to commitment, caring and spirituality. Conclusion: Commitment was an important aspect for increasing caring behavior. The spirituality will be a good approach to build cadres’ awareness of mental disorder condition and have a good effect in caring behavior.